Investment Literacy in Personal Financial Management Planning for Students of Brawijaya University - Endang Sri Apriani; Kety Lulu Agustin; Anisya Sukmawati; Dessy Handa Sari; Nurul Musfirah Khairiyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Control over the consumptive behavior of students in the coffee shop era. This drives students to incur more expenses as a form of existence, but it can also be a positive thing if the gatherings can be measured and discussed financially. This research examines how students who have acquired knowledge about investments manage their consumption levels towards good financial planning. The research findings indicate that students who understand finance are better able to control their consumption desires and tend to invest. Students also plan to be disciplined in investing. Thus, the financial education they receive in their studies has a positive impact on managing their consumption desires and tends to lead to more effective investment in financial planning.